Estudo da ocorrência e dos fatores determinantes da obesidade em trabalhadoras - Distrito Industrial da Zona Franca de Manaus, Am – Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2002)
The present study investigates the occurrence of obesity and its interaction with social, economic and environmental factors as well as eating habits of workers of factories of the Industrial District of the Manaus Free Zone, state of Amazonas – Brazil.The studied universe was composed of 159 women with a mean age of 35 years. Their nutritional state was evaluated through anthropometrics measurements and complemented by biochemical analyses. The BMI – Body Mass Index (W/H2), waist circumference, hip circumference and Waist-hip Ratio has been used.For the biochemical evaluation the total cholesterol, HDL-c, LDL-c, VLDL-c , triglycerides and glucose have been measured. The information about living conditions, social economic, environmental and cultural profile and physical activity of workers has been collected trough questionnaires. As to eating habits, a 24-hour recall of investigation was established. The anthropometrics variables show the occurrence of (2,5%) of malnutrition Degree( I ), (37,7%) of overweight and (20,2%) of obesity. The BMI shows rising values when the number of pregnancies rises. Circumferences of waist and hip increased, showing a waisthip ratio compatible with android obesity, being more expressive in the age of group of 40 to 60 years. The biochemical analyses stay within normal patterns. There are, however total cholesterol values of (201,8 mg/dL) and (202,1 mg/dL) in the age groups of 30 to 39 and 40 to 49 years respectively. Correlating the biochemical variables to the BMI we observe that border values of (208,0 mg/dL) and (217,0 mg/dL) and the obesity ranges degree I and II respectively. The LDL-c (134,9mg/dL) and (142mg/dL) in the ranges of the BMI compatible with Eutrophy and obesity degree II were noted.The analyses of the main factors of the nutritional status shows the occurrence of overweight in workers with good housing conditions, stable married life, and income of three minimum salaries or more and over nine years of schooling. The evaluation of physical activity points to a sedentary life style of the majority (91,8%) studied. He analyses of 24-hour recall emphasizes the consumption of constructor foods, such as: jerked meat (42,1%), Jaraqui fish (61,0%), e cottage cheese (34,0%); regulator foods: Açaí palm fruit (26,0%),and raw or cooked vegetables (37,1%). Among the energetic foods, soybean oil (96,2%) stands out. The foods researches show a carbohydrate intake below the recommended level and fat and proteins above the recommendation RDA/89. The intake of foods rich in fibers reveals an adequate percentage (42,9%). The intake of foods rich in sodium is above the adequate percentage as recommended by RDA/89 (187,9%). The cholesterol values are within the recommended level of 300mg per day. The total caloric value showed a percentage of (77,3%) which is below the recommendation of RDA/89.
Keywords: Antropometria; Padrão alimentar; Epidemiologia; Obesidade; CIENCIAS AGRARIAS: CIENCIA E TECNOLOGIA DE ALIMENTOS: CIENCIA DE ALIMENTOS